2017
DOI: 10.1038/ncomms14982
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanics of individual aerographite tetrapods

Abstract: Carbon-based three-dimensional aerographite networks, built from interconnected hollow tubular tetrapods of multilayer graphene, are ultra-lightweight materials recently discovered and ideal for advanced multifunctional applications. In order to predict the bulk mechanical behaviour of networks it is very important to understand the mechanics of their individual building blocks. Here we characterize the mechanical response of single aerographite tetrapods via in situ scanning electron and atomic force microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…In Fig. 3f , stress–strain curves for 3D CNTT structures having a CNT concentration of 0.10 g cm −3 and 0.12 g cm −3 are depicted together with results of numerical simulation 49 . The corresponding conductivity curves for the two samples are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Fig. 3f , stress–strain curves for 3D CNTT structures having a CNT concentration of 0.10 g cm −3 and 0.12 g cm −3 are depicted together with results of numerical simulation 49 . The corresponding conductivity curves for the two samples are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The samples have a square-shaped surface with a lateral size L = 2 cm, a thickness d = 0.2 cm, and a mass m = 5 − 15 mg. A representative sample is reported in Figure 1a. From the scanning electron microscopy (SEM) micrograph in Figure 1b, a random network made of micrometer-sized carbon tetrapods [23][24][25] constituting the aerogel surface (Figure 1b, inset) can be observed. This particular shape is due to the precursor ZnO template employed during the material synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the influence of the sintering time and temperature [9, 10] on the morphology and feature of the NPs were deeply investigated. Moreover, it is found that the leaching processes [11, 12] as well as capping agents [4, 7] pave the way for the tuning size. The obtained results have demonstrated that the tailoring size and shape can improve the magnetic characteristics, governed by Snoek's law [7, 13, 14].…”
Section: Introductionmentioning
confidence: 99%